6b+0=-4b+29

Simple and best practice solution for 6b+0=-4b+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6b+0=-4b+29 equation:


Simplifying
6b + 0 = -4b + 29

Reorder the terms:
0 + 6b = -4b + 29
Remove the zero:
6b = -4b + 29

Reorder the terms:
6b = 29 + -4b

Solving
6b = 29 + -4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4b' to each side of the equation.
6b + 4b = 29 + -4b + 4b

Combine like terms: 6b + 4b = 10b
10b = 29 + -4b + 4b

Combine like terms: -4b + 4b = 0
10b = 29 + 0
10b = 29

Divide each side by '10'.
b = 2.9

Simplifying
b = 2.9

See similar equations:

| 1.9x+6=3.1-x | | 4x+27=195 | | 3n+12+n-6=24 | | 6n-15=2n+21 | | (P-3)(3p+1)=0 | | 108+256x^3=0 | | 4x+9-3x-4= | | 81+18b+b^2= | | 0.4=x | | (4+7)(5y+7)=0 | | 6(3+8x)=-318 | | -2(5x-6)-(3x+3)= | | 8(.06m+21.80+.20(21.80))=241.92 | | -13c-35=9-2e | | 8x+7=6x+35 | | 2(4g-3)-8=4+2x | | 3x+27=195 | | -6(3w+5)+3w+5=w-45 | | 1(21)-2=19 | | n-(-12)=23 | | 10x+9-11-X=-4x-8-6x-6 | | 7p^2=17p-6 | | 65x+74=2089 | | (6x-1)-(10x-15)=0 | | 15=1+16t-4t^2 | | x+2x-3=5 | | 8(z+2)-4(3z+1)= | | 9(2n-2)=(4n+2)+1 | | 3x+6=393 | | 36.71=11.11+3.4t | | 27x^2+9y^2=0 | | 20x=10y+8 |

Equations solver categories